ANALYZE REFRIGERATOR TOOLING INVESTMENT LIVIA MODEL AT PT LG ELECTRONICS INDONESIA - Apit Supriyadi; Mini Wijaya; Tedy Fardiansyah (Bina Nusantara University, 2008)
For a large firm like PT LG Electronics Indonesia (LGEIN), which has resulted in high manufacturing utilization, require a few percent reductions in component prices every year. The one of potential project for cost reduction is tooling investment. After Livia is produced and the expenditure of new tooling is made, it is continually faced with the problem that current method computing profits are conventional without considering the expenditure of tooling in the long run. Finally, a firm’s capital budgeting decisions is needed because it defines its strategic direction. Four primary methods in the capital budget to decide whether or not the project should be accepted are: discounted payback, net present value, internal rate of return and profitability index. In addition, we use sensitivity analysis to indicate which factor has significant interfere with the project. The results generated that discounted payback is just 2 year 6 months less life of the project for 3 years, NPV generated positive result 3,502,387, and an IRR of this project is 25% greater than required rate of return 10% and profitability index gets 1.8 greater than 1. In sensitivity analysis shows that the project’s NPV is very sensitive to changes in sales and COGS, and relatively insensitive to changes in either growth rate or rate of return.In a method of capital budgeting analysis, Livia project could be accepted with initial investment for 4,199,288 and still more detailed analysis is required to support the expenditure.